Relational factors of EHR database in visual analytic systems for public health care units - Malik, M.S.A. (Springer Verlag, 2013)
Information Visualization (IV) in Electronic Health Records (EHR) is a significant source of patient knowledge using available medical data set(s). Although IV applications most focus on demands of doctors as considering primary stake holders for this use but unavailability of simplified, ease to use and a user friendly application is due to non-consideration and absence of database contextual factors in EHR tools development. Efficient query handling and data retrieval is carried out using various visual health data related queries based on structure and hierarchical flow of event based information. Conventional visual EHR applications ignore the fact of heterogeneity within the different data entities, i.e., text, number, figure and other form of data and more focus on presentation of data rather than considering the pre alignment and configuration of database affecting results. This research work is carried out solely for highlighting the needs of database professional and influencing factors affecting the efficacy of query based visualization results in EHR. More emphasis is on future needs of database professionals point of view in context of developing a Visual Analytic System that can address the needs of doctors and other stake holders based on capacity and performance ability of given database based on encoupled factors. It also represents the gaps areas of databases within visualizations and determines the solution by providing highly demanded scope areas for visualization in EHR. This will yield to a contribution to formulate database model within ongoing research for CARE1.0 as a complete EHR visualization model. Â© Springer International Publishing Switzerland 2014.